2023
DOI: 10.1111/sum.12932
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry potential for adaptation to climate change: A soil‐based perspective

Abstract: Agricultural systems face several challenges that threaten their capacity to feed the world while maintaining a healthy and functional environment. Climate change, together with soil degradation, biodiversity loss, resource scarcity and invasive species, is a major threat to agricultural systems worldwide. In this context, new practices have been proposed to circumvent or minimize these threats. Yet, these mostly focus on the farm or plant level (e.g., breeding for stress‐tolerant species), while frequently ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 256 publications
(352 reference statements)
0
8
0
Order By: Relevance
“…(2020) and V. Rolo et al (2023). Scientists advocate for fundamental changes in the legal regulation of stabilizing components of agroecosystems by achieving their optimal ratio, sustainable functioning, and increased productivity.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) and V. Rolo et al (2023). Scientists advocate for fundamental changes in the legal regulation of stabilizing components of agroecosystems by achieving their optimal ratio, sustainable functioning, and increased productivity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies of whole soil profile, it was found that structural quality of the lower part of the soil profile (50-75 cm and 75-100 cm layers) is primarily because of the characteristics of the parent rock. On the contrary, the structural quality of the 0-25 cm and 25-50 cm layers is determined by the type of plant vegetation and the corresponding ecological conditions that are formed under plant influence (Belova & Travleev, 1999;Gritsan, 2000;Rolo et al, 2023). When comparing the VESS (Sq) scores of the studied sites (Table 1), it can be noted that their average values for the Sites 4-6 (native forest) do not statistically differ from each other, but they are lower than the average scores for the Sites 1-3 (wildland and shelterbelts).…”
Section: Discussionmentioning
confidence: 99%
“…Intensive land management, however, causes nutrient losses and impairs the physical and structural properties of soils of the steppe landscapes of Ukraine (Baliuk et al, 2021;Medvedev et al, 2014;Ponomarenko et al, 2022). Introduction and improvement of agroforestry techniques were demonstrated to be efficient strategies to counteract soil degradation, as they enable creation of an environmentally sustainable land use system based on the integration of natural forests into the agricultural landscape; they usually involve the creation of man-made forest plantations having various functional purposes (Pantera et al, 2021;Plieninger et al, 2020;Rolo et al, 2023). As a result of intensive agricultural use of lands in the steppe zone, natural steppe herbaceous vegetation has been preserved only on territories designated for conservation and protection of natural environments and, fragmentarily, in small areas inconvenient for agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of agroforestry to improve soil properties through fresh organic matter inputs and soil organic carbon increases, thereby increasing the system's capacity to cope with unfavourable edaphoclimatic conditions, is well reported in the literature, e.g., [32,[86][87][88]. In fact, because AFS can support adaptation to climate change by improving ES, these sys-tems were incorporated into the National Adaptation Plans of several developing countries.…”
Section: Soil Quality Indicators and Soil Ecosystem Servicesmentioning
confidence: 99%